Liberia : Staff Report for the 1999 Article IV Consultation and Staff-Monitored Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Liberia has begun the long process of recovery and rehabilitation after the civil war. The government should expand its focus from near-term relief and reconstruction to a more comprehensive reconstruction and economic reform program. The government remains committed to its economic and financial program monitored by IMF staff. The continuation of an appropriately restrained monetary stance, supported by a tight fiscal position, is important to build confidence in both the central bank and the new currency, and should allow for a gradual increase in international reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet